The Myths We Live By - Midgley, Mary (Taylor & Francis, 2003)
Mary Midgley argues in her powerful new book that far from being the opposite of science, myth is a central part of it. In brilliant prose, she claims that myths are neither lies nor mere stories but a network of powerful symbols that suggest particular ways of interpreting the world.